Analysis of the fitness characteristic in the training process of the international spanish players - Pazo, C.; Fradua, L.; Saenz-Lopez, P. (7th World Congress on Science and Football (WCSF), 2011, 2011)
In this stydy we try to know, in the area related to the phyisical training, the opinion and relevance that confer the players and the different responsible people in the development process of the players to each of the fitness characteristics to become an international player. In order to do this, we have interviewed the responsible people of the different sectors involved in the training of some of the best clubs in which the players of the Spanish national team, the current world champion, have been trained. Methods We have inteviewed 11 players of the nacional team, 7 academy directors, 7 fitness coaches, 5 doctors and 6 psycologists. Each of them, from their own approach, have offered their opinion. The data collected in the interviews were analysed with the program MAXQDA2007. We have used a qualitative methodology, widely used in Sport Science, and particulary in the development of the training of players. Durand-Bush & Salmela (2002). Results & Discussion Speed is the physical quality more quoted, and with the highest degree of importance. 29 profesionals mention it in their interviews, 23 of them emphasize it as the most important one. The doctors, however, consider that resistance is more definitive in order to achieve the national team at the highest level. Strength has been less considered, probably because it is related to a structural improvement of the muscle and not as a basic quality of speed. Le Gall et al. (2010) think that there was also a difference in counter-movement jump and 40-m sprint time in internationals versus amateurs. Conclusion The most important physical quality to become an international player at the highest level is speed.